The Use of Journalistic Language in Writing Religious Rubrics in the Malut Post Newspaper - Ali, Siti Mutiah; Rifa’i, Akhmad (Jurnal Ilmiah Mandala Education (JIME), 2024)
The Wisdom of Ramadan rubric is a religious rubric owned by the Malut Post Newspaper. The purpose of this study is to find out how journalistic language is used in writing religious rubrics in the Malut Post newspaper and what mistakes are often made in writing this rubric. This research uses content analysis method, with filling system technique by Wimmer and Dominick. From the research conducted, there are research results, namely (1) the use of journalistic language in writing religious rubrics in the Malut Post newspaper is in accordance with the use of journalistic language, and has followed journalistic writing standards but not perfectly. Therefore, it cannot be denied that there are still mistakes that occur in writing religious rubrics. (2) There are several mistakes made repeatedly in writing religious rubrics such as the use of capital letters, wasting words, writing EYD/KBBI, clarity of messages, mistakes in using punctuation marks, and mistakes in using italics. Therefore, with this research, print media should have repeated and detailed checks in accordance with journalistic language or good and correct language.